Food-borne zoonoses their impact on food safety - Baldrias, Loinda R. (2001)
Food-borne zoonoses (FBZs) are diseases transmissible from animals to man via the medium of foods derived from animals such as meat, poultry, fish and shellfish, milk and food by-products. The total number of people affected (at least 17 million worldwide each year) and the harm caused by FBZs make them a serious public health concern. Food-borne intoxication and food-borne infection emphasize the inextricable link between animal and human health activities that share the common ultimate goal of protecting, promoting and improving the health and well-being of human populations. Thus, problems of contamination in specific animal production or processing operations need to be identified and the process of contamination understood. Food handlers and consumers should be made aware of the dangers of and the methods for reducing the risk from zoonoses. The paper outlines the simple measures that consumers can apply to protect themselves from FBZs.
Keywords: Zoonoses; Food safety